Viral particles drive rapid differentiation of memory B cells into secondary plasma cells producing increased levels of antibodies. - Zabel, F; Mohanan, D; Bessa, J; Link, A; Fettelschoss, A; Saudan, P; Kündig, T; Bachmann, M (American Association of Immunologists, 2014)
Extensive studies have been undertaken to describe naive B cells differentiating into memory B cells at a cellular and molecular level. However, relatively little is known about the fate of memory B cells upon Ag re-encounter. We have previously established a system based on virus-like particles (VLPs), which allows tracking of VLP-specific B cells by flow cytometry as well as histology. Using allotype markers, it is possible to adoptively transfer memory B cells into a naive mouse and track responses of naive and memory B cells in the same mouse under physiological conditions. We have observed that VLP-specific memory B cells quickly differentiated into plasma cells that drove the early onset of a strong humoral IgG response. However, neither IgM(+) nor IgG(+) memory B cells proliferated extensively or entered germinal centers. Remarkably, plasma cells derived from memory B cells preferentially homed to the bone marrow earlier and secreted increased levels of Abs when compared with primary plasma cells derived from naive B cells. Hence, memory B cells have the unique phenotype to differentiate into highly effective secondary plasma cells.